Clinical application status and prospect of the combined anti-tumor strategy of ablation and immunotherapy - Yin, Li; Li, Xing-yu; Zhu, Lin-lin; Chen, Gui-lai; Xiang, Zhuo; Wang, Qing-qing; Bi, Jing-wang; Wang, Qiang (Frontiers in Immunology, 2022)
Image-guided tumor ablation eliminates tumor cells by physical or chemical stimulation, which shows less invasive and more precise in local tumor treatment. Tumor ablation provides a treatment option for medically inoperable patients. Currently, clinical ablation techniques are widely used in clinical practice, including cryoablation, radiofrequency ablation (RFA), and microwave ablation (MWA). Previous clinical studies indicated that ablation treatment activated immune responses besides killing tumor cells directly, such as short-term anti-tumor response, immunosuppression reduction, specific and non-specific immune enhancement, and the reduction or disappearance of distant tumor foci. However, tumor ablation transiently induced immune response. The combination of ablation and immunotherapy is expected to achieve better therapeutic results in clinical application. In this paper, we provided a summary of the principle, clinical application status, and immune effects of tumor ablation technologies for tumor treatment. Moreover, we discussed the clinical application of different combination of ablation techniques with immunotherapy and proposed possible solutions for the challenges encountered by combined therapy. It is hoped to provide a new idea and reference for the clinical application of combinate treatment of tumor ablation and immunotherapy.